Comparison of the Visual Analog Scale and Oswestry Disability Index between Working and Non-Working Women with Lower Back Pain: VAS and Oswestry Disability Index Between Women with Lower Back Pain - Khan, Tanzeela; Qayoom, Abdul; Ahmed, Noman; Naz, Anum; Ghulam, Hussain (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2025)
Low back pain (LBP) is one of the most prevalent musculoskeletal disorders worldwide, significantly affecting women’s daily activities, functional capacity, and quality of life. Occupational status may play an important role in influencing pain perception and disability outcomes. Objectives: To compare the scores of the VAS and OID between working and non-working women with low back pain. Methods: This study involved 356 participants, particularly women with LBP, of whom 178 were employed and 178 were unemployed. Subjects were included if they were women with non-specific LBP and met the required age range and employment status criteria. Exclusion criteria were being male, having a particular medical condition, deformities, or having undergone recent surgery. The subjects were recruited from offices and different homes in Karachi. All the participants were informed and provided written consent before participating in the study. The institutional review board or ethics committee gave the study ethical approval. Results: The average age of the participants was 31.16 years for both the working and the non-working women. Two groups did not differ significantly (p=0.826>0.05) in terms of VAS score. The ODI score, however, proved that there was a statistically significant difference (p=0.034<0.05), indicating that there was more functional restriction in one group. Conclusions: The study concluded that both working and non-working women experience functional limitations and pain due to low back pain, with significant differences in disability levels measured by ODI.